2019
DOI: 10.2478/msp-2019-0077
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, morphology, electrical conductivity and electrochemical properties of α-Ni(OH)2 and its composites with carbon

Abstract: A simple and effective hydrothermal synthesis of spherical α-Ni(OH)2 particles and α-Ni(OH)2/carbon composites was proposed. The mechanism of ultrafine α-Ni(OH)2 phase forming and correlations between synthesis conditions, morphology, electrical conductivity were analyzed. It was found that carbon nanoparticles form an electric conductive cover on nickel hydroxide microparticles during synthesis which increases overall electronic conductivity of the composite material. α-Ni(OH)2 and α-Ni(OH)2/C samples were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…3). In electrochemical studies of α and β phases of nickel hydroxide [17,18] was found that the oxidation peaks lie in the range of 0.29-0.5 V for both phases, while the cathodic reduction peaks at 0.24 V for β-Ni(OH)2 and 0.16 V for α-Ni(OH)2, which agrees with the results obtained for initial NiMoO4 in this work.…”
Section: Resultssupporting
confidence: 90%
“…3). In electrochemical studies of α and β phases of nickel hydroxide [17,18] was found that the oxidation peaks lie in the range of 0.29-0.5 V for both phases, while the cathodic reduction peaks at 0.24 V for β-Ni(OH)2 and 0.16 V for α-Ni(OH)2, which agrees with the results obtained for initial NiMoO4 in this work.…”
Section: Resultssupporting
confidence: 90%
“…In [152,153] β‐hydroxide nickel/carbon composites were obtained and investigated. β‐Ni(OH) 2 /reduced graphene oxide composites [154–156] were also actively investigated, including the production of nickel hydroxide by ammonia precipitation in the presence of PEG600 [154] and hydrothermal synthesis [155] . In, [157] the authors studied α‐Ni(OH) 2 and its composites with carbon.…”
Section: Application Fields Of Nickel Hydroxides: Required Properties...mentioning
confidence: 99%
“…β-Ni(OH) 2 /reduced graphene oxide composites [154][155][156] were also actively investigated, including the production of nickel hydroxide by ammonia precipitation in the presence of PEG600 [154] and hydrothermal synthesis. [155] In, [157] the authors studied α-Ni(OH) 2 and its composites with carbon. Film electrodes deposited on an electrically conductive base were also studied, including by electrochemical [158] and chemical decomposition methods with Co activation.…”
Section: Hybrid Supercapacitormentioning
confidence: 99%
“…Nanostructured materials deserve much of attention due to their unique electrochemical, optical, magnetic, electrical and photocatalytic properties [1,2]. Nowadays among different ways of applying nanomaterials there is a significant increase of their application in energystorage devices due to the increasing public demand for them.…”
Section: Introductionmentioning
confidence: 99%